Assessment of Absorption of Glycated Nail Proteins in Patients with Diabetes Mellitus and Diabetic Retinopathy - Ieva Jurgeleviciene; Daiva Stanislovaitiene; Vacis Tatarunas; Marius Jurgelevicius; Dalia Zaliuniene (Medicina, 2020)
Background and objectives: Glycation occurs in a variety of human tissues and organs. Knowledge about the relationship between predictive biochemical factors such as absorption of glycated nail proteins and severity of type 2 diabetes mellitus (DM) and diabetic retinopathy (DR) remains limited. Materials and Methods: The study group consisted of patients with type 2 DM and DR (n = 32) and a control group (n = 28). Each patient underwent a comprehensive ophthalmic examination. The glycation process in nail clippings was evaluated in stages of in vitro glycation and deglycation stages. ATR–FTIR spectroscopy was used to calculate the infrared absorption in the region of interest. The absorption of solutions with nail clippings was evaluated by NanoDrop spectrophotometry. Absorption spectra differences before and after the exposure to fructosamine 3-kinase were compared between DM patients with DR and the control group. Results: The absorption of glycated nail protein greater than 83.00% increased the chance of developing DM and DR (OR = 15.909, 95% CI 3.914–64.660, p < 0.001). Absorption of glycated nail protein by ATR–FTIR spectroscopy in patients with DM and DR in vitro glycation was statistically significantly higher than in the control group; also absorption of solution with nails by NanoDrop spectroscopy was statistically significantly higher than in controls in vitro glycation and in vitro deglycation. After exposure to fructosamine 3-kinase, absorption of nail protein in DM + severe/proliferative DR group was statistically significantly lower in comparison with DM + mild/moderate group DR. Conclusions: Evaluation of glycated nail protein could be applied to evaluate the risk of having DM and for long-term observation of DM control.